1995
DOI: 10.1007/bf01276505
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine effect on synthesis rate of serotonin in the monkey brain measured with positron emission tomography

Abstract: The influence of the co-factor pyridoxine, vitamin B6, on the activity of aromatic amino acid decarboxylase enzyme was studied by positron emission tomography, PET in the brain of the Rhesus monkey using the precursor for serotonin synthesis 5-hydroxy-L-tryptophan (5-HTP) radiolabelled with 11C in the beta-position. The rate constant for the formation of serotonin in the corpus striatum was calculated using a two tissue compartment model with reference area in the brain. In baseline investigations, the mean ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 22 publications
0
31
2
2
Order By: Relevance
“…Breads and fortified breakfast cereals are good sources of the B vitamins thiamin and pyridoxine. These vitamins assist in attentional processes, synthesis of neurotransmitters and carbohydrate metabolism (41,42) . As B vitamins are water-soluble, body stores are relatively small and can decline over a period of a few weeks in the absence of sufficient dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…Breads and fortified breakfast cereals are good sources of the B vitamins thiamin and pyridoxine. These vitamins assist in attentional processes, synthesis of neurotransmitters and carbohydrate metabolism (41,42) . As B vitamins are water-soluble, body stores are relatively small and can decline over a period of a few weeks in the absence of sufficient dietary intake.…”
Section: Discussionmentioning
confidence: 99%
“…A further explanation to the effect of vitamin B-6 on insulin response to a glucose load might be linked to its role in decarboxylation of tryptophan to serotonin. Indeed, in rats, it has been shown that B-6 supplements can stimulate serotonin synthesis in the brain (Hartvig et al 1995), although the effects would be more marked after concommitant supplements of B-6 and tryptophan (Lee et al 1988). Additional studies are needed to investigate the importance of this metabolic pathway because of the role of this amine on insulin secretion and sensitivity (Furman and Waton 1989).…”
Section: Response To Duodenal Infusion Of Glucose or Glucose + Tryptomentioning
confidence: 99%
“…Other nutrients which are altered in patients with major depression and that can influence neurotransmitter production include tryptophan (and other large neutral amino acids: valine, leucine, isoleucine, phenylalanine and tyrosine) (Maes et al, 2011c, Markus, 2008, Toker et al, 2010, folic acid (Miller, 2008, Stahl, 2008, zinc , Szewczyk et al, 2011, vitamin B12 (Bottiglieri, 1996, Deana et al, 1977), vitamin B6 (Calderon-Guzman et al, 2004, Demisch and Kaczmarczyk, 1991, Hartvig et al, 1995 and iron (Baumgartner et al, 2012, Burhans et al, 2005, Coe et al, 2009). Omega-3 EFAs are also able to modify monoaminergic neurotransmission (Chalon, 2006, Su, 2009).…”
Section: Diet and Its Effect On Neurotransmittersmentioning
confidence: 99%